2018
DOI: 10.1039/c8gc02805b
|View full text |Cite
|
Sign up to set email alerts
|

Techno-economic assessment for the large-scale production of colloidal lignin particles

Abstract: Economical large-scale production of colloidal lignin particles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 32 publications
1
46
0
Order By: Relevance
“…Development of green technologies [74,75] for the preparation of bio(nano)materials [76] from the forest process side-streams such as adhesives and coatings [77,78] is increasing constantly. Different CLPs prepared and modified to adhere chamois and to modify CNF surface could be potential additives for various formulations to be exploited for wound sealing, edible coatings and fiber modification for textiles to improve adhesion, hydrophobicity, antimicrobial and antioxidative properties of the coatings.…”
Section: Discussionmentioning
confidence: 99%
“…Development of green technologies [74,75] for the preparation of bio(nano)materials [76] from the forest process side-streams such as adhesives and coatings [77,78] is increasing constantly. Different CLPs prepared and modified to adhere chamois and to modify CNF surface could be potential additives for various formulations to be exploited for wound sealing, edible coatings and fiber modification for textiles to improve adhesion, hydrophobicity, antimicrobial and antioxidative properties of the coatings.…”
Section: Discussionmentioning
confidence: 99%
“…They found that one of the hot spots was the thermal energy needed for ethanol recovery, which is in accordance to the techno economical assessment of another solvent shifting process that also found that solvent recovery was the most energy demanding step during lignin particle production. 183 That calculation was made for THF : ethanol : water system. However, recently Lourençon et al found that using acetone : water as solvent in the atomization process the reactor did not need to be heated for solvent evaporation and lignin concentration up to 5% could be used.…”
Section: Sustainability Aspectsmentioning
confidence: 99%
“…In applications that require large volumes of particles the production process needs to be scalable. The techno-economical feasibility of production processes has been evaluated for both dry 41 and wet approaches 183 and both are scalable. For the wet approach, the most energy consuming steps are the drying of particles and recycling of the solvents.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…The low extent of commercialization of lignin is mainly due to its complex and inhomogeneous structure resulting from different sources and extraction processes (Li et al, 2015). However, recent studies have shown that fabricating spherical micro- or nanoparticles from lignin not only enables the large scale utilization of lignin (Ago et al, 2016; Leskinen et al, 2017a; Ashok et al, 2018; Lintinen et al, 2018), but also improves properties such as surface activity, antioxidative, UV shielding, and antimicrobial activity for potential high-value applications (Beisl et al, 2017).…”
Section: Introductionmentioning
confidence: 99%